PERAN PENDIDIK PAI DALAM PENGEMBANGAN PEMBELAJARAN AGAMA YANG INKLUSIF DI SEKOLAH - Munadi, Muhammad (IAIN Ponorogo, 2012)
Abstract: This research was aimed to reveal the religious inclusivism contents on Islamic Education subject taught at senior high school level, learning model of Islamic Religious Education is taught in secondary education pursue the development of tolerance and religious inclusivism on the learners and the teachers and instructional materials provide inspire for learners to develop attitudes of tolerance and religious inclusivism. Type of research is qualitative research methods. Subjects Research and Sources of Data in this study is the teachers of Islamic education on SMAN 4 Surakarta. Setting in this study took place in Surakarta, who have a variety of Islamic dynamics that are considered to be moderate to radical. Data collection techniques used were: In-depth Interviews, participant observation, and documentation. The validity of data used in this research are triangulation methods and sources. The data analysis was done by following the interactive model analysis of Miles and Huberman consisting of collecting the data, reducing the data, describing the data, and making conclusion and verification. Result of the research showed that the content of religious tolerance and inclusivism is taught in class XI semester 1 and 2 are expressly or directly relate to other religions or indirectly, the model simulation in concept (analysis of the teaching program) exists, but not operationalized at the level of material and learning . But in the great Day of Islam, students are encouraged to appreciate the opinions of others and the inspiration to develop attitudes of tolerance and religious inklusifisme contained in textbooks through the verses of the nuances of this, such as Surat al-Baqara verse 285 and Surah Al Hujurat paragraph 13.